2021
DOI: 10.1002/admt.202100016
|View full text |Cite
|
Sign up to set email alerts
|

A Soft Touch: Wearable Tactile Display of Softness Made of Electroactive Elastomers

Abstract: Fingertip‐mounted tactile displays of softness are needed for various virtual‐ or augmented‐reality applications such as surgical simulation, tele‐operation, computer‐aided design, 3D model exploration, and tele‐presence. Displaying a virtual softness on a fingertip requires the generation of quasi‐static large displacements at moderate forces (as opposed to high‐frequency small vibrations at high forces), via a deformable surface, to control both the contact area and the indentation depth of the skin. State‐o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…These advancements have led to the achievement of high mechanical output force of up to 2 N and large displacements of up to 9.3 mm (Figure ). ,, The high force and large displacement capabilities of soft actuators have made them valuable for practical applications, including haptic displays and soft grippers. , …”
Section: Soft Actuators For Haptic Feedbackmentioning
confidence: 99%
See 3 more Smart Citations
“…These advancements have led to the achievement of high mechanical output force of up to 2 N and large displacements of up to 9.3 mm (Figure ). ,, The high force and large displacement capabilities of soft actuators have made them valuable for practical applications, including haptic displays and soft grippers. , …”
Section: Soft Actuators For Haptic Feedbackmentioning
confidence: 99%
“…57 These advancements have led to the achievement of high mechanical output force of up to 2 N and large displacements of up to 9.3 mm (Figure 14). [56][57][58]357,358 The high force and large displacement capabilities of soft actuators have made them valuable for practical applications, including haptic displays and soft grippers. 359,360 DEAs offer several advantages, including a large strain of 503%, 361 fast operation with a frequency of 280 Hz, 362 and lightweight characteristics.…”
Section: Soft Actuators For Tactile Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…The actuator was composed of a thin plastic pouch containing a low-boiling-point liquid. The maximum output force of the actuator could reach almost 1.5 N. Carpi et al [19] reported a nonvibratory display of softness made of electroactive polymers. It consisted of a hydrostatically coupled dielectric elastomer actuator, shaped as a bubble interfaced to the fingertip, having a weight of 6 g. Prototypes could generate displacements up to 3.5 mm and forces up to 1 N. Leroy et al [20] proposed multimode hydraulically amplified electrostatic actuators for wearable haptics.…”
Section: Introductionmentioning
confidence: 99%